Experimental and numerical investigation of gap K-joints of rectangular hollow section trusses - Faycal Slimani; Mohammed Benzerara; Messaoud Saidani (Fracture and Structural Integrity)
This paper is concerned with investigating the plastic behavior of gap K-joints of truss girders, made from thin-walled rectangular hollow section members. The novelty of the method is that it offers a rigorous numerical model that may be generalized to cover similar joints with different parameters to the one covered in this study. An experimental study was carried out on a full-scale girder under concentrated load on two central nodes. A numerical analysis was carried out using ABAQUS to investigate the behavior of this type of joints and comparison is made with the experimental results. The study aims to examine and define the analytical model for this type of joints. The results obtained show that sections with chord/brace thickness ratio (t0/t1)=1 exhibit a different behavior compared to sections with (t0/t1)>1. From this study, it was possible to obtain the modes of failure of such sections followed by a comparative study on the determination of the joint capacity using Eurocode 3 and CIDECT